Preventive Measures in the Treatment of Caries in School children - Qurbonova Mahliyo Tavakalova; Burxonova Zarafruz Qobilovna; Yakubova Sarvinoz (Genius Journals, 2023)
In many countries of the world in the last 20–30 years, there has been a decrease in the prevalence and intensity of dental caries in children [1]. This phenomenon of the late XX - early XXI century coincides with the widespread introduction of systemic fluoridation programs (USA, Germany, France, etc.) and local application of fluoride to teeth in the form of varnishes, gels and toothpastes (Scandinavian and Baltic countries). Of particular note are fluoride-containing toothpastes, whose consumption has increased by 29.7% since 2000 in the world, by 45.4% in Western Europe, and by 90.6% in Eastern Europe [2]. Recognizing the fact that the decrease in the intensity of carious disease coincides with the increase in the consumption of fluoride-containing toothpastes in general, one cannot but notice the minimal effect of global fluoridation of toothpastes on the inhabitants of Eastern Europe and Russia. In Uzbekistan, the average citizen annually consumes about 300 ml of toothpaste (G. N. Pakhomov, 2006). However, the medical effect of this method of prevention of dental caries is small: the average index of the permanent teeth KPU (reflecting the number of carious, filled and extracted teeth in one individual) in 12-year-old children living in the territory of the Uzbekistan is 2.5. Similar dynamics is observed in the CIS countries [3], which is about 2 times higher than in the USA and 2.6 times higher than in Germany [4]. From the above data it follows that the total fluoridation of toothpastes does not solve the problem of dental caries properly. One of the possible reasons for the insufficient anti-carious effectiveness of hygiene products may be a formal attitude to oral hygiene and the lack of perception of it as an important factor in prevention, not only of dental diseases, but also of the so-called seasonal infections, exacerbations of chronic diseases. Meanwhile, modern medicine has confirmed this connection. Regular and thorough oral care leads to a decrease in the frequency of common diseases, especially colds and allergies
Keywords: connection; fluoridation; territory; hygiene